Research in the history of economic thought and methodology : including a symposium on Bruce Caldwell's Beyond Positivism after 35 years - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology ;, 2018)
Volume 36A of "Research in the History of Economic Thought and Methodology" features a symposium on Bruce Caldwells "Beyond Positivism" after 35 years. Contributors to the symposium include Kevin Hoover, Wade Hands, Tony Lawson, and Peter Boettke. The volume also features general-research essays from Luis Mireles-Flores and Alain Marciano. Luca Fiorito presents a new discovery from the archives.